PEMANFAATAN Azolla sp. UNTUK PENURUNAN KANDUNGAN COD DALAM LIMBAH LAUNDRY - Ammelia Mentari; Namastra Probosunu; Ratih Ida Adharini (Jurnal Perikanan Universitas Gadjah Mada, 2016)
This research aims to know the ability of Azolla sp. to improve the water quality of laundry wastewater based on COD. This research applied 6 treatments with 3 replications using Completely Randomize Design (CRD) analysis. The treatment consists of P0 (0 gram), P1 (50 gram), P2 (100 gram), P3 (150 gram), and P4 (200 gram) which was placed in a tank that contains 30 liters of laundry wastewater with 50% dilution. The parameters of water quality such as COD, pH, water temperature, and biomass were being observed in every 7 days for 21 days. The result showed that Azolla sp. has the ability to improve the quality of the water from laundry wastewater, especially in lowering the COD level. The results showed that the laundry wastewater’s COD decreases from 133,43 mg/L to 41,52 mg/L. The density and the effective time of Azolla sp. in improving the quality of laundry wastewater is on 7 days of 150 gram treatment or 14 days of 50 gram treatment